Experimental and Theoretical Investigation of the Structural and Opto‐electronic Properties of Fe‐Doped Lead‐Free Cs(2)AgBiCl(6) Double Perovskite - Thawarkar, Sachin (Chemistry, 2021)
Lead‐free double perovskites have emerged as stable and non‐toxic alternatives to Pb‐halide perovskites. Herein, the synthesis of Fe‐doped Cs(2)AgBiCl(6) lead‐free double perovskites are reported that display blue emission using an antisolvent method. The crystal structure, morphology, optical properties, band structure, and stability of the Fe‐doped double perovskites were investigated systematically. Formation of the Fe‐doped Cs(2)AgBiCl(6) double perovskite is confirmed by X‐ray diffraction (XRD) and X‐ray photoelectron spectroscopy (XPS) analysis. XRD and thermo‐gravimetric analysis (TGA) shows that the Cs(2)AgBiCl(6) double perovskite has high structural and thermal stability, respectively. Field emission scanning electron microscopy (FE‐SEM) analysis revealed the formation of dipyramidal shape Cs(2)AgBiCl(6) crystals. Furthermore, energy‐dispersive X‐ray spectroscopy (EDS) mapping shows the overlapping of Cs, Bi, Ag, Fe, and Cl elements and homogenous incorporation of Fe in Cs(2)AgBiCl(6) double perovskite. The Fe‐doped Cs(2)AgBiCl(6) double perovskite shows a strong absorption at 380 nm. It extends up to 700 nm, suggesting that sub‐band gap states transition may originate from the surface defect of the doped perovskite material. The radiative kinetics of the crystals was studied using the time‐correlated single‐photon counting (TCSPC) technique. Lattice parameters and band gap value of the Fe‐doped Cs(2)AgBiCl(6) double perovskites predicted by the density functional theory (DFT) calculations are confirmed by XRD and UV/Visible spectroscopy analysis. Time‐dependent photo‐response characteristics of the Fe‐doped Cs(2)AgBiCl(6) double perovskite show fast response and recovery time of charge carriers. We believe that the successful incorporation of Fe in lead‐free, environmentally friendly Cs(2)AgBiCl(6) double perovskite can open a new class of doped double perovskites with significant potential optoelectronics devices fabrication and photocatalytic applications.